The Role of the Tourism Office in Managing the Suban Air Panas Tourism - Saputra, Ade Marta; Aminudin, Achmad; Yogopriyatno, Jatmiko (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
This study aims to analyze the lack of role of the Tourism Office of Rejang Lebong Regency in managing the Suban Air Hot Tourism. The method used in this research is descriptive qualitative. The results of the study show that in the motivating aspect it is known that the ability of the Tourism Office in mobilizing other people does not play an optimal role, it can be seen from the socialization that is carried out indirectly, guidance and training that is less successful, strengthening tourism promotion which is not carried out massively this is due to budget constraints . In the aspect of the Facilitator shows that the existing facilities and infrastructure at the Suban Air Hot Tourism object look rundown and there has been no increase in terms of facilities and infrastructure, this is due to budget constraints. In the Dynamics aspect, it shows that the Tourism Office's ability to synergize parties that can help tourism development, for example the community, government and the private sector do not play an optimal role, seen in the absence of the private sector or investors coming in because of the regional regulation number 30 concerning levies. The researcher concluded that the role of the Pariwsata Service in the management of Hot Air Suban tourism in Rejang Lebong Regency did not play an optimal role. As for recommendations for the Rejang Lebong Regency Tourism Office to conduct socialization directly to the community, provide guidance and training on a regular basis and guide until they can, promote Suban Air Hot Tourism with interesting content and involve influencers, improve facilities and infrastructure, review Regional Regulations Number 30 concerning tourism fees, implementing a public private partnership to manage the Suban Air Panas Tourism.